Discordance between pain and radiographic severity in knee osteoarthritis: Findings from quantitative sensory testing of central sensitization. Issue 2 (28th January 2013) - Finan, Patrick H.; Buenaver, Luis F.; Bounds, Sara C.; Hussain, Shahid; Park, Raymond J.; Haque, Uzma J.; Campbell, Claudia M.; Haythornthwaite, Jennifer A.; Edwards, Robert R.; Smith, Michael T.
Abstract Objective Radiographic measures of the pathologic changes of knee osteoarthritis (OA) have shown modest associations with clinical pain. We sought to evaluate possible differences in quantitative sensory testing (QST) results and psychosocial distress profiles between knee OA patients with discordant versus congruent clinical pain reports relative to radiographic severity measures. Methods A total of 113 participants (66.7% women; mean ± SD age 61.05 ± 8.93 years) with knee OA participated in the study. Radiographic evidence of joint pathology was graded according to the Kellgren/Lawrence scale. Central sensitization was indexed through quantitative sensory testing, including heat and pressure–pain thresholds, tonic suprathreshold pain (cold pressor test), and repeated phasic suprathreshold mechanical and thermal pain. Subgroups were constructed by dichotomizing clinical knee pain scores (median split) and knee OA grade scores (grades 1–2 versus 3–4), resulting in 4 groups: low pain/low knee OA grade (n = 24), high pain/high knee OA grade (n = 32), low pain/high knee OA grade (n = 27), and high pain/low knee OA grade (n = 30). Results Multivariate analyses revealed significantly heightened pain sensitivity in the high pain/low knee OA grade group, while the low pain/high knee OA grade group was less pain‐sensitive. Group differences remained significant after adjusting for differences on psychosocial measures, as well as age, sex, and race. Conclusion The results suggest that central sensitization in knee OA is especially apparent among patients with reports of high levels of clinical pain in the absence of moderate‐to‐severe radiographic evidence of pathologic changes of knee OA.